Role of TLR2‐dependent IL‐10 production in the inhibition of the initial IFN‐γ T cell response to Porphyromonas gingivalis. Issue 1 (1st January 2013) - Gaddis, Dalia E.; Maynard, Craig L.; Weaver, Casey T.; Michalek, Suzanne M.; Katz, Jannet
Abstract : IL‐10 produced by T cells and CD11b + cells utilizes TLR2 signaling and FimA antigen to inhibit early IFN‐γ T cell responses to Porphyromonas gingivalis . Abstract : P.g ., a Gram‐negative bacterium, is one of the main etiological agents of the chronic inflammatory disease, periodontitis. Disease progression is thought to occur as a result of an inadequate immune response, which although happens locally, can also occur distally as a result of the dissemination of P.g . into the circulation. As IL‐10 and TLR2 are pivotal molecules in the immune response that P.g . elicits, we hypothesized that TLR2‐mediated IL‐10 production, following the initial systemic exposure to P.g ., inhibits the IFN‐γ T cell response. To address this hypothesis, mice were primed with P.g ., and the types of cells producing IL‐10 and the capacity of T cells to produce IFN‐γ following blocking or neutralization of IL‐10 were assessed. Our results showed that upon initial encounter with P.g ., splenic T cells and CD11b + cells produce IL‐10, which when neutralized, resulted in a substantial increase in IFN‐γ production by T cells. Furthermore, IL‐10 production was dependent on TLR2/1 signaling, partly in response to the major surface protein, FimA of P.g . In addition, P.g . stimulation resulted in the up‐regulation of PD‐1 and its ligand PD‐L1 on CD4 T cells and CD11b + cells, respectively. Up‐regulation of PD‐1 was partially dependent on IL‐10 but independent of TLR2 or FimA. These results highlight the role of IL‐10 in inhibiting T cell responses to the initial systemic P.g . exposure and suggest multiple inhibitory mechanisms potentially used by P.g . to evade the hostˈs immune response, thus allowing its persistence in the host.